Diseases of the esophagus and stomach: the evolution of doctors’ attitudes to the psychosomatic aspects of clinical manifestations and treatment (Journal of Science-Innovative Research in Uzbekistan, 2024)
The lecture discusses the stages of evolution of theoretical ideas about psychosomatization in the development of diseases of the upper digestive tract, and discusses practical issues of diagnosis and treatment of patients with functional disorders